2011
DOI: 10.4236/jbpc.2011.22018
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of bovine serum albumi with two alkylimidazolium-based ionic liquids investigated by microcalorimetry and circular dichroism

Abstract: The interactions of bovine serum albumin (BSA) with two alkylimidazolium-based ionic liquids, 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim]BF 4 ) and 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim]PF 6 ), in buffer solutions at pH 7.0 were investigated by isothermal titration calorimetry (ITC) and circular dichroism (CD). CD spectra showed that the two ionic liquids changed the secondary structure of BSA. Data process was based on the supposition that there were several independent types of bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…However, our study, which including a relatively broad spectrum of imidazolium cations, clearly revealed the higher affinity of longchain ILs to HSA, and hence, their binding at even lower IL concentration might be related also to interaction with the hydrophobic domains (IIA and IIIA) of HSA. The fact that ILs interact with the protein through both electrostatic and hydrophobic interactions has been confirmed by other studies (Zhang et al 2018;Geng et al 2009Geng et al , 2010Mester et al 2010;Pei et al 2012;Yan et al 2012;Cao et al 2014;Wang et al 2012;Zhu et al 2011;Singh et al 2012;Bharmoria et al 2014).…”
Section: Determining the Percentage Of Ionic Liquid Bound To Proteinsupporting
confidence: 64%
“…However, our study, which including a relatively broad spectrum of imidazolium cations, clearly revealed the higher affinity of longchain ILs to HSA, and hence, their binding at even lower IL concentration might be related also to interaction with the hydrophobic domains (IIA and IIIA) of HSA. The fact that ILs interact with the protein through both electrostatic and hydrophobic interactions has been confirmed by other studies (Zhang et al 2018;Geng et al 2009Geng et al , 2010Mester et al 2010;Pei et al 2012;Yan et al 2012;Cao et al 2014;Wang et al 2012;Zhu et al 2011;Singh et al 2012;Bharmoria et al 2014).…”
Section: Determining the Percentage Of Ionic Liquid Bound To Proteinsupporting
confidence: 64%
“…There are enough evidences in literature which conclude that 4 the interaction between protein and IL depends on the protein as well as on the cations and anions present in the ILs. [19][20][21][22][23] Studies have shown ammonium-based ILs to act as better stabilizing agent for proteins as compared to imidazolium-based ILs. 24 Our research group has out carried protein stability studies in both ammonium and imidazolium-based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…These investigations suggest that there is no fixed rule which can predict the behavior of protein in ILs. There is enough evidence in the literature that concludes that the interaction between a protein and IL depends on the protein as well as on the cations and anions present in the ILs. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, several ILs are proved to be stabilizers for the enzymes and proteins, in some cases even up to 100 °C, while in some cases denaturation with loss of enzyme activity. Moreover, ILs having imidazolium cations have earned special attention in the field of protein stabilities. A study by Yan et al on the interaction of [C 4 mim]­[Br] and [C 8 mim]­[Br] with β-casein micelles shows that partitioning of IL molecules in different locations of β-casein micelles was dependent upon concentration and chain length of the IL.…”
Section: Introductionmentioning
confidence: 99%